Relationship Between Stunting and Caries In Children Aged 2-5 Years Old Systematic Review - Devi Ridha Oktashafa; Hema Awalia; Mellani Cindera Negara; Martha Mozartha (Sriwijaya Journal of Dentistry, 2023)
Introduction: Stunting is a chronic nutritional deficiency caused by a deficiency of macronutrients and micronutrients. Nutritional deficiency in stunting children affects the occurrence of salivary gland atrophy, changes in saliva composition, and changes in mineral content in teeth that are at risk for dental caries. Purpose: To determine the relationship between stunting and dental caries in children aged 2-5 years old. Methods: The type of research is a systematic review with qualitative analysis. Result: This study involved five journals that were selected from the PUBMED journals database and Google Scholar. Cross-sectional and experimental journals within the last 15 years discussing relationship between stunting and dental caries in children aged 2-5 years old. Conclusion: There is a relationship between stunting and dental caries (n=5).